Revealing the Relationship of Batik Motifs Using Convolutional Neural Network - Najar, Abdul Mahatir; Abu, Maulidyani; Ratianingsih, Rina; Jaya, Agus Indra (Sistemasi: Jurnal Sistem Informasi, 2024)
This study explores the use of Convolutional Neural Network to identify and classify regional batik motifs, a significant aspect of Indonesian cultural heritage. The CNN model was optimized with Adam optimizer and used to extract distinctive features from the batik patterns. Subsequently, a hierarchical clustering method was employed to construct a relationship tree depicting the link between batik motifs based on their region. The research findings demonstrate that the CNN model effectively classifies batik motifs with an accuracy of up to 88%. The study provides insights into the intricate connections between regional batik designs and contributes to the preservation and understanding of Indonesia's cultural heritage.